The impact of HIV on severe childhood malnutrition - De Maayer, Tim (My University, 2010)
Aim: Case fatality rates for child severe malnutrition have remained high globally and in South Africa. It has been postulated that much of this excess mortality is due to HIV infection. This study sought to examine case fatality rates in children with and without HIV infection, and with different forms of malnutrition. Methods: A prospective, observational study was undertaken at three academic hospitals in Johannesburg, South Africa. Severely malnourished children were identified and their anthropometric details, clinical features, laboratory findings and admission outcomes analysed. Nutritional status was categorised using the Wellcome and WHO classifications. All children had their HIV status established. Results: The case fatality rate in 113 severely malnourished children was 11.5%. Fifty one percent of children were HIV infected. Most (44%) of children had kwashiorkor, with 26% having marasmus and 20% classified as marasmic kwashiorkor. HIV positive children were significantly more likely to die than negative children (19% vs 3.6%, OR 6.2, 95% CI 1.2–59, p=0.02). Marasmic children were more likely to have HIV than those with kwashiorkor or marasmic kwashiorkor (83% vs 33%, OR 9.7, 95% CI 3.5–29.1, p< 0.001). Half (51%) of all HIV negative children whose mother’s status was known had an HIV positive mother. TB was suspected and treated in 24% of children, although confirmed in only 19% of these. Factors associated with an increased mortality included hypothermia (OR 9.7), hypoglycaemia (OR 9.7), shock (OR 7.2), thrombocytopaenia (OR 5.7), raised INR (OR 9.8) and the intravenous administration of fresh frozen plasma or packed red blood cells (OR 9.7 and 7.8 respectively). Conclusion: The HIV pandemic has altered the face of malnutrition in the study setting. Case fatality rates remain unacceptably high in HIV positive malnourished children. Specific guidelines for the management of severe malnutrition in HIV positive children and improved tuberculosis, growth monitoring and growth promotion programmes could reduce this impact.
MMed (Paediatrics), Faculty of Health Sciences, University of the Witwatersrand
Keywords: malnutrition; children; HIV